Comparative Analysis of Innovative PV Microgrids in Paris and Nice, France - Ya, Aung Ze (European Journal of Sustainable Development, 2016)
This present research addresses the mix of the two innovative ideas: the focus on the DC loads for avoiding the conventional conversion losses in the building and the comparative analysis between the innovative Grid-connected PV Microgrid models in two different French Cities, Paris and Nice. The DC load profile of the Office and the proposed models can also demonstrate the enhancement of the sustainability by saving the Energy Consumption and Energy Charges as well as the reduction of GHG Emissions. The modeling and simulation are performed in HOMER Pro (Version 3.6.2). The techno-economic results of the optimistic models are beneficial for the planning and the implementation of PV Microgrid projects at the buildings in nowadays Green Revolution. Key Words: PV Microgrid models, Paris, Nice, HOMER Pro, DC Office